Linagliptin use in older individuals with type 2 diabetes - Pratley RE (Dove Medical Press, 2014)
Richard E Pratley1–31Florida Hospital Diabetes Institute, 2Translational Research Institute for Metabolism and Diabetes, 3Sanford-Burnham Medical Research Institute, Orlando, FL, USAAbstract: Older people have the highest prevalence of type 2 diabetes mellitus (T2DM) of any age group and are thus frequent users of glucose-lowering agents. Because individuals 65 years or older are underrepresented in clinical studies, there is a lack of information regarding the efficacy and safety of available treatments in this population. Additionally, a high prevalence of comorbidities, polypharmacy, and frailty can make treatment of T2DM in this population challenging. Safety is an important consideration when choosing a treatment for older individuals. Renal impairment is quite common in older patients with T2DM and can contribute to hypoglycemia. Hypoglycemia can lead to serious consequences, such as falls and fractures, and cognitive changes. As such, hemoglobin A1c treatment targets, typically <7% in the general population, are less stringent in older people, with the goal being an individualized target that balances efficacy and safety. Many glucose-lowering agents can cause adverse events detrimental to older individuals, such as hypoglycemia (insulin, sulfonylureas), weight gain (sulfonylureas, thiazolidinediones), gastrointestinal events (metformin), and fractures (thiazolidinediones), and are contraindicated or require dose adjustments in those with renal impairment (most oral/injectable agents). Orally administered dipeptidyl peptidase (DPP)-4 inhibitors have a low risk of hypoglycemia and are generally well tolerated. Linagliptin is the only DPP-4 inhibitor excreted through nonrenal pathways and therefore does not require any dose adjustment in older patients with kidney disease. This paper reviews the findings of a recent study by Barnett et al assessing the efficacy and safety of the DPP-4 inhibitor linagliptin in patients with T2DM aged 70 years or older, which concluded that linagliptin may be a useful glucose-lowering option for older patients with T2DM.Keywords: DPP-4 inhibitors, clinical trial, renal impairment, hypoglycemia